Is the Craft-Making Materials in Elementary School Student Books 2013 Curriculum Suitable with 3R (Reduce, Reuse, Recycle) Principles? - Wihana, Hari; Syaodih, Ernawulan (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
The amount of damage that has been caused by waste as a form of human indifference to the environment requires real action to deal with it. Various efforts have been made to reduce waste in Indonesia. One of which is to integrate the principles of 3R waste management (reduce, reuse, and recycle) in the materials for making handicrafts in elementary schools. This study aims to analyze the suitability of the material for making handicrafts with the 3R principle. This study uses a qualitative descriptive research method with content analysis techniques. The data source is the Student Book for 1st grade to 6th of elementary school Curriculum 2013. The research instrument used is a checklist containing the criteria for the suitability of craft-making materials with 3R principles. The results showed that the material for making handicrafts in the elementary school student books was very suitable with the 3R principles. 1st grade has a suitability category of 61.11%, 2nd grade is 75%, 3rd grade is 100%, 4th grade is 83.33%, 5th grade is 100%, and 6th grade is 83.33%. So that the overall suitability of all grades is 83.78%, which means the material is very suitable with the 3R principle.